PERAN TITIK-TITIK PERTALIAN DALAM MENENTUKAN HUKUM YANG BERLAKU PADA SENGKETA PERDATA INTERNASIONAL - Damanik, Yohana Dwi Putri; Zendrato, Oktafiani; Septaria, Ema (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
International Civil Law is a law that regulates the relationship between individuals and legal entities in different countries. This legal relationship can be referred to as a relationship with other countries but in a civil context. Through current developments, especially the activities of every community are not only carried out in their own country but there are also problems that can occur among foreign countries. For example, the issue of marriage between different countries. In this issue, this will raise legal issues which will have an impact on which law applies between the two countries in resolving the problems that occur, which in this case the issue in question is a matter of civil law. Before resolving an international civil dispute, it must first determine which law applies to the case at hand, meaning that it must determine the point of connection (determining link point). After determining the linking point, a way of resolving the international civil dispute will be obtained.